One year follow-up and exploratory analysis of a patient-centered interdisciplinary care intervention for multimorbidity - Martin Fortin MD, MSc; Moira Stewart PhD; José Almirall MD, PhD; Djamal Berbiche; Mathieu Bélanger PhD; Alan Katz MB, ChB, MSc; Bridget L Ryan PhD; Sabrina T Wong RN, PhD; Merrick Zwarenstein MB, BCh, PhD (Journal of Multimorbidity and Comorbidity)
Context Interventions for people with multimorbidity have obtained mixed results. We aimed to document the long-term effect of an intervention for people with multimorbidity. Methods 284 patients (18–80 years) presenting three or more chronic conditions were recruited from seven family medicine groups in the Saguenay-Lac St-Jean region, Quebec, Canada. The patient-centered intervention was based on motivational approach and self-management support. Outcomes were evaluated in a one-year pre-post study design with questionnaires that included the Health Education Questionnaire (heiQ), the Self-Efficacy for Managing Chronic Diseases, the Veteran RAND-12 Health Survey (VR-12), the EuroQoL 5-Domains questionnaire, the Kessler six item Psychological Stress Scale, and measures of smoking habit, physical activity, healthy eating and alcohol consumption. Subgroup analyses by age, number of conditions, sex, and income were also conducted. Results The heiQ domain of emotional wellbeing improved significantly. Improvement was also observed for the VR-12 and the K6. Among the health behaviours, only healthy eating was improved. Subgroup analyses in this exploratory study suggest that younger patients, those with lower number of chronic conditions or higher incomes may respond better in relation to self-management, health status and health behaviours. Conclusion One year after the intervention, participants significantly improved a variety of outcomes. Subgroup analyses suggest that younger patients, those with lower number of chronic conditions or higher incomes may respond better in relation to self-management, health status and health behaviours. This suggests that future interventions should be tailored to patients’ characteristics including age, sex, income and number of conditions.